2020
DOI: 10.1109/tii.2019.2908989
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Multiobjective Optimization for Burden Surface in Blast Furnace With Feedback Compensation

Abstract: In this paper, an intelligent data-driven optimization scheme is proposed for finding the proper burden surface distribution, which exerts large influences on keeping blast furnace running smoothly in energy-efficient state. In the proposed scheme, production indicators prediction models are firstly developed using kernel extreme learning machine algorithm. To heel, burden surface decision is presented as a multi-objective optimization problem for the first time and solved by a modified two-stage intelligent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The radial distribution of the charged solid raw materials, i.e., burden surface (see the right top corner of Fig. 1), influences the pressure loss and the local mass flows of solid and gas inside the furnace, and further affects the indirect reduction degree of the ore [15]. In addition, the burden surface is closely related to operating status.…”
Section: A Bf Ironmaking Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The radial distribution of the charged solid raw materials, i.e., burden surface (see the right top corner of Fig. 1), influences the pressure loss and the local mass flows of solid and gas inside the furnace, and further affects the indirect reduction degree of the ore [15]. In addition, the burden surface is closely related to operating status.…”
Section: A Bf Ironmaking Processmentioning
confidence: 99%
“…Finally, the closeness coefficient C * i is calculated using Eq. (15). Ranking all the alternatives according to C * i and the optimal solution is obtained.…”
Section: B Optimization Strategy For Burden Surface Based On Mode Anmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze gas flow distribution and optimize burden distribution matrix, Huang et al composed a high temperature industrial endoscope to measure the 3D burden surface of BF [7]. Li et al found a different way to analyze the burden surface distribution by intelligent datadriven optimization scheme [8]. All of these approaches have partially explained the behaviors of BF, but the ironmaking process is in need of more information to optimize its operation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with physical experiments, mathematical modeling [3] has gained popularity due to its lower cost and higher flexibility. The mathematical modeling approaches [4,5] regarding the BF burden distribution (corresponding to the bell-less charging system) can basically be categorized as volume-based simplified models or classical (continuum) force models [6][7][8][9][10][11][12][13][14], data-driven models [15,16], or hybrid models [17,18], as well as the more computationally expensive models based of the discrete element method (DEM) [19][20][21][22][23]. Among these models, the classical force model has advantages in terms of its simple model formulation and fast computation, which are readily suitable for online implementation.…”
Section: Introductionmentioning
confidence: 99%